Efficacy and Safety of Supracostal Puncture in Percutaneous Nephrolithotomy - Wahaj, Ahmed; Rauf, Abdul; Rehman Khan, Fazal Ur; Azhar, Muhammad Hamza; Hussain, Nuzhat Faqir; Hasan, Muhammad Yahya (Biological and Clinical Sciences Research Journal, 2025)
Percutaneous nephrolithotomy (PCNL) is the standard treatment for large renal stones. The supracostal puncture approach offers improved access to the upper calyces and may enhance stone clearance, but concerns remain regarding thoracic and bleeding complications. Local data evaluating the efficacy and safety of supracostal PCNL in Pakistan are limited. Objective: To determine the efficacy and safety of supracostal puncture in patients undergoing percutaneous nephrolithotomy. Methods: This descriptive study was conducted at the Department of Urology, Shaikh Zayed Hospital, Lahore, over six months, from 11 April to 11 October. A total of 100 patients aged 20–70 years undergoing supracostal PCNL were enrolled using non-probability consecutive sampling. Efficacy was defined as complete stone clearance on KUB CT at 4 weeks. Safety outcomes included bleeding, haematuria, pneumothorax, and overall complications graded according to the Clavien Dindo classification. Data were analyzed using SPSS version 25. Stratification was performed, and chi-square tests were applied with a significance level of p ≤ 0.05. Results: The mean age was 45.8 ± 12.6 years, with male predominance (68%). Stone-free status was achieved in 78% of patients. Overall complications occurred in 31%, with bleeding being the most frequent (27%), followed by haematuria (9%) and pneumothorax (3%). Most complications were Clavien Dindo Grade I or II, while Grade IIIa complications occurred in 3% of patients. No Grade IIIb or higher complications were observed. Stratification analysis showed that efficacy was significantly higher in patients with a stone size <3 cm, shorter stone duration, single stones, and no diabetes mellitus. Postoperative bleeding was significantly associated with stone size ≥3 cm, longer stone duration, and diabetes mellitus. Conclusion: Supracostal puncture PCNL is an effective and relatively safe approach for the management of renal stones when performed in appropriately selected patients, with acceptable complication rates and favorable stone clearance outcomes.